C-reactive protein levels and periodontal diseases during pregnancy in Malaysian women - Ahmad, Aisah; Nazar, Zeyad; Swaminathan, Dasan (Quintessence Publishing, 2018)
Purpose: To investigate the association between plasma CRP levels and periodontal disease during pregnancy. Materials and Methods: Fifty-six pregnant women attending the Antenatal Clinic, UMMC for their first antenatal check-up consented and were recruited for this study: 28 subjects with diseased periodontium (test group) and 28 subjects with healthy periodontium (control). The test group underwent nonsurgical periodontal therapy and the control group was given oral hygiene education. Periodontal parameters and CRP levels were evaluated at baseline and 6 weeks. Pregnancy outcome data were recorded from the Antenatal Clinic, UMMC. Results: Plasma CRP levels in the test group were statistically significantly elevated compared to the control group (8.55 ± 5.28 mg/l vs 5.66 ± 2.91 mg/l). After nonsurgical periodontal therapy, a statistically significant reduction in the CRP level in the test group (2.06 mg/l) along with statistically significant improvement in periodontal status in both groups was observed. The mean birth weight for infants of both groups showed no statistically significant difference. Conclusions: Plasma CRP levels in pregnant women with diseased periodontium were statistically significantly reduced after nonsurgical periodontal therapy. However, no association between CRP levels and adverse pregnancy outcome was observed.